The Effect of Pharmaceutical Service Quality on Patient Satisfaction at UPtd Puskesmas Kamonji Palu Using the Servqual Method (Service Quality) - Muh. Sandy Putra; Nur Afni; Rosnawati Rosnawati (Universitas Muhammadiyah Palu, 2020)
Pharmacy is a pharmacy service facility where pharmacists practice pharmacy. To improve pharmaceutical services in pharmacies, it is necessary to evaluate by assessing patient satisfaction. This study is an attempt to determine the effect of the quality of pharmacy services at the Kamonji Palu Health Center on patient satisfaction and to measure the performance of pharmaceutical services to improve public health services. This type of research is quantitative with a cross-sectional approach, and the sampling method is an accidental sampling. The analytical tool used is a simple linear regression analysis test and Cartesian diagram analysis with a total sample of 96 people. The results of regression research show that the variables have a positive effect but has no significant impact on patient satisfaction, namely the Tangible variable with a significance value of 0.119> 0.05, Reliability with a significance value of 0.494> 0.05, Responsiveness with a significance value of 0.113> 0.05, Assurance with a significance value of 0.918> 0.05, Empathy with a significance value of 0.222> 0.05, at this moment the quality of pharmacy services at the Kamonji Palu Health Center get positive results but have no significant effect on patient satisfaction. In contrast, the results of the Cartesian diagram analysis are nine items included in the quadrant. I, four things belong to quadrant II, six items belong to quadrant III, and six items belong to quadrant IV. The conclusion is that pharmaceutical services at the Kamonji Community Health Center are good but not significantly influencing patient satisfaction with suggestions to improve further and pay attention to patient comfort.